GIS-based Geospatial Risk Modeling of Extreme Waves and Abrasion on the West Coast of Sumatra - Simarmata, Nirmawana; Wijayanti, Goldie Melinda; Nadzir, Zulfikar Adlan; Al Farishi, Bilal; Hendrawan, Rezki Naufan (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Indonesia, with its second-longest coastline in the world, is vulnerable to coastal disasters such as extreme waves and coastal abrasion. Pesisir Barat Regency in Sumatra is one of the regions that is vulnerable to these threats. Extreme waves, although rarely occur because of tropical cyclones, can be triggered by the influence of cyclones in the Indian Ocean. In addition, coastal abrasion caused by the interaction of waves, currents, and winds is increasingly threatening coastal areas. This research aims to identify the risk of extreme waves and abrasion disasters in Pesisir Barat Regency using a research-based approach to Geographic Information Systems (GIS) and multi-criteria analysis. Data on marine hydrodynamics, coastal topography, and land cover conditions are integrated to produce disaster risk maps. The risk analysis results show that the Ngaras sub-district and several other sub-districts, such as Bangkunat, Lemong, and Ngambur, have a high level of risk, with a total risk area reaching 0.398 square kilometers (km2). Meanwhile, most other sub-districts are in the low-risk class. Key factors influencing the risk level include coastal topography, vegetation cover, and the intensity of human activities in coastal areas. This study highlights the importance of coastal zone management based on risk mitigation and the need to protect coastal ecosystems to reduce disaster impacts. The findings are expected to serve as a reference for disaster mitigation policy planning in Pesisir Barat and other coastal areas. Additionally, these results could be utilized to develop holistic and practical disaster reduction effort by related stakeholders and coastal communities.